2014
DOI: 10.1007/s00300-014-1621-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vent systems on pelagic eukaryotic micro-organism composition in the Nordic Seas

Abstract: Deep-sea hydrothermal vents and cold seeps are biological hot spots with chemolithotrophic bacterial production sustaining both benthic and pelagic organisms. Although efforts have been made to understand the diversity and function of the bacterial composition of these systems, first-level consumers, pelagic single cell heterotrophic organisms, which represent an important link between bacterial production and higher trophic levels, remain un-described in hydrothermal vents and seeps of the Nordic Seas. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…Previous studies also demonstrated that no obvious geographical difference was found for prokaryotic abundance in fluids (10 3 to 10 5 cells mL −1 ) or sediments (10 7 to 10 8 cells g −1 ) in the shallow-water hydrothermal systems ( 36 ) and deep-sea vents ( 37 ). In addition, the microeukaryotic abundance revealed in our study was much higher than that in the deep-sea pelagic waters ( 38 ), which might due to the increased food availability for microeukaryotes in hydrothermal fluids and chimneys ( 16 , 39 ). Since this is the first report about microeukaryote abundance in the deep-sea vents, further proof will be needed to confirm their high abundance.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous studies also demonstrated that no obvious geographical difference was found for prokaryotic abundance in fluids (10 3 to 10 5 cells mL −1 ) or sediments (10 7 to 10 8 cells g −1 ) in the shallow-water hydrothermal systems ( 36 ) and deep-sea vents ( 37 ). In addition, the microeukaryotic abundance revealed in our study was much higher than that in the deep-sea pelagic waters ( 38 ), which might due to the increased food availability for microeukaryotes in hydrothermal fluids and chimneys ( 16 , 39 ). Since this is the first report about microeukaryote abundance in the deep-sea vents, further proof will be needed to confirm their high abundance.…”
Section: Discussioncontrasting
confidence: 51%
“…6). Such differences could be due to extraction, primer, and/or sequencing bias (Brooks et al, 2015;VerBerkmoes et al, 2009); limited references in taxonomic databases (Orellana et al, 2019); or biological differences in cellular pools of RNA and proteins. Regardless, both analyses indicate that at a coarse taxonomic level, particle-associated prokaryotic Table 3.…”
Section: Microbial Community Composition In Background and Hydrothermally Influenced Seawatermentioning
confidence: 99%
“…Deep sea communities therefore may be relying on metabolic plasticity to exploit a variety of environmental conditions, enabling the occupation of both hydrothermal and non-hydrothermal influenced seawater systems. Protistan groups such as ciliates, stramenopiles, dinoflagellates and radiolarians are also ubiquitous in the deep ocean, and may serve as important vectors for transferring carbon obtained from vent sites to the broader bathypelagic ocean (Olsen et al 2015;Murdock and Juniper 2019;Mars Brisbin et al 2020). However, hydrothermal populations can be genomically distinct from background communities at a fine taxonomic level, which has been observed in vent-influenced protistan communities using amplicon sequence variants (ASVs) (Mars Brisbin et al 2020;Hu et al 2021) and bacterial functional genes (Mino et al 2013(Mino et al , 2017, although this was not observed here using an OTU approach.…”
Section: Microbial Community Composition In Background and Hydrothermally-influenced Seawatermentioning
confidence: 99%